Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus

Selective and generic photocatalytic oxidation of alcohol with Pd-TiO2 thin films: butanols to butanal/butanone with different morphologies of Pd and 0.5 theta(Pt)-Pd counterparts - Salgaonkar, Kranti N.; Kale, Sandip R.; Nalajala, Naresh; Mansuri, Sayana; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2023)
The present study reports on the photocatalytic oxidation of butanols to butanal/butanone using thin film form of facet-dependent nano-Pd supported on commercial TiO2 under one-sun condition and demonstrates the generic nature. Pd-nanocube (Pd-NC(100)), Pd-truncated octahedron (Pd-TO (100) and (111)), polycrystalline (Pd-PC), and their counterparts with half-a-monolayer Pt-coated on Pd (0.5 theta(Pt)-Pd)) have been used as co-catalyst. A potentially scalable thin film form of Pd/TiO2 photocatalyst, prepared by drop-casting method, has been employed to study oxidation of n-butanol, 2-butanol, and iso-butanol to corresponding aldehyde/ketone. 100% selectivity is demonstrated to respective aldehyde/ketone with any catalyst used in the present study with varying degree of butanols conversion by NMR. 0.5 theta(Pt)-Pd-TO/TiO2 shows the highest conversion of 2-butanol to butanone (13.6% in 4 h). Continuous 10 h of reaction with the most active 0.5 theta(Pt)-Pd-TO/P25 catalyst demonstrates 31% conversion of 2-butanol to butanone, and catalyst recyclability has been demonstrated. The present protocol can be scalable to large scales to maximize the conversion in direct sunlight. Due to its generic nature, the current method can also be applied to many other alcohols and substrate molecules.
Keywords: energy conversion; Nanomaterials; Oxidation; Photocatalysis; Sustainability

Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting

Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting

Selective anodic transformation of glycerol with ZnCo 2 O 4 2D nanoplates: sustainable coproduction of carbon-negative green hydrogen and formic acid - Saha, Arindam; Murugiah, Vasantharadevi; Kollenteakathootu, Jayalakshmi; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2025)
In the pursuit of sustainable green hydrogen production, the electrooxidation of abundantly available carbon-containing molecules at a significantly low voltage presents a promising pathway, helping to reduce the cost of hydrogen generation while simultaneously yielding value-added chemicals/fuels. In the current study, we report the template-free green synthesis of ZnCo2O4 directly on Ni-foam (NF), demonstrating anodic stability and bifunctional electrocatalytic activity toward alkaline (1 M KOH) glycerol oxidation over an extended duration of 230 h at 50 mA cm- 2. The catalyst's high electrochemical surface area contributes to its remarkable performance, enabling sustained high current density. Compared with monometallic (ZnO or Co3O4) oxides, ZnCo2O4 oxide reveals superior catalytic performance. The two-electrode electrolyzer setup (ZnCo2O4 oxide/NF || ZnCo2O4 oxide/NF) operates at a significantly low cell potential of 1.9 V to achieve 100 mA cm- 2 in 0.2 M glycerol, which is 180 mV lower than that of conventional 1 M KOH solution. The three-electrode setup achieved 1 A/cm2 current density at 1.907 V vs RHE. Both anodic and cathodic processes exhibit high Faradaic efficiency, achieving 98% efficiency for H2 and 90% selectivity toward formate generation, along with significant methanol production. This demonstrates efficient C-C bond cleavage capability with glycerol to predominantly C1-products. The electrocatalytic formate production from alkaline glycerol using ZnCo2O4 offers an energy-efficient pathway, facilitating carbon-negative green hydrogen generation, thus contributing to a cleaner and sustainable energy landscape.
Keywords: energy conversion; Formic acid; glyceroloxidation; green H-2; water electrolysis

Visible-light-driven photocatalytic glycerol oxidation to value-added and highly selective glyceric/lactic acid - Kulkarni-Sambhare, Mukta; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S. (ChemiCatChem, 2025)
Achieving economical and sustainable artificial photosynthesis (APS) in direct sunlight for liquid fuel production with high efficiency remains an important challenge. A major obstacle in the photoelectrochemical (PEC) oxidation of organic compounds is attaining high selectivity with the desired product(s). This study introduces a novel strategy by integrating BiVO4 quantum dots (BVQDs), structurally and electronically, into the nanopores of commercial TiO2 (BVT for BVQDs integrated in pores of TiO2) to improve solar-driven photocatalysis. The band gap of the BVT photoanode decreases to 2.53 eV as compared to pure TiO2 (3.2 eV), which enhances visible light absorption and charge separation. BVT with Pt as a co-catalyst acts as an APS system, which selectively oxidizes glycerol into lactic acid (100% selectivity at 1 mM glycerol) and glyceric acid (98% selectivity at 100 mM), while simultaneously generating green hydrogen. Selectivity of the product can be further controlled by anaerobic or aerobic conditions as well as the length of the reaction time. Direct integration of BVQDs into TiO2 mesopores significantly enhances charge separation as well as utilization at redox sites. Current work provides key insights into optimizing photocatalytic conditions for highly selective value-added chemical production, which highlights the sustainability and efficacy of TiO2-based semiconductors with quantum dot integration.
Keywords: energy conversion; Energy storage; Photocatalysis; Quantum material; solar energy

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability